2018
DOI: 10.5539/jfr.v8n1p12
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Physicochemical, Nutritional and Sensory Quality Characteristics of New Papaya Hybrids Fruits Developed in JKUAT

Abstract: The world is faced with a lot of challenges including lack of sustainable development and inability to feed its growing population leading to malnutrition. The issue of accessing high quality nutritious foods such as fruits has become a major challenge for many African people. Papaya (Carica papaya L.) is among the most popular fruits grown in Kenya and excellent in nutritional content. However, its potential has remained unexploited due to inadequate quality planting materials, high post- harvest losses and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The fruits' peel and flesh hue angles changed over the storage duration; similar results were observed by Caron et al (2013) as the papaya fruits' hue angles decreased after storing the fruits from day 0 to 30 days at both 5 and 10 ˚C. The visual sensation of fruit colors is the core factor that influences customer preferences upon the purchase of mature and ripe fruits (Ruslan et al, 2016) and is an indicator of freshness and flavor quality (Nishimwe et al, 2018). Both Mountain and F fruits had desirable amber flesh colors after 8 days of storage.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The fruits' peel and flesh hue angles changed over the storage duration; similar results were observed by Caron et al (2013) as the papaya fruits' hue angles decreased after storing the fruits from day 0 to 30 days at both 5 and 10 ˚C. The visual sensation of fruit colors is the core factor that influences customer preferences upon the purchase of mature and ripe fruits (Ruslan et al, 2016) and is an indicator of freshness and flavor quality (Nishimwe et al, 2018). Both Mountain and F fruits had desirable amber flesh colors after 8 days of storage.…”
Section: Discussionsupporting
confidence: 67%
“…Total soluble solids for both papaya fruits increased with an increase in temperature and duration, reducing total titratable acidity and resulting in increased TSS:TTA ratios. A research study by Nishimwe et al (2018) reported that consumer acceptance of papaya fruits depends on physicochemical properties like TSS; F fruits would be more desirable to consumers compared to Mountain Fruits as they had more TSS and less TTA. Naturally, papaya is a sweet and low-acid fruit; hydrolysis of its starch to sugars as it advances in maturation has been explained as a reason behind the increase in TSS (Benkeblia et al, 2011) and low TTA values at the end of its shelf life (Falah et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These factors are also affected by different genetic constitution of different lines which are key and directly responsible for expression of genetic characters under a particular set of environment (Bhandari et al, 2017). The total soluble solids varied significantly among the papaya lines which was also reported by Nishimwe et al (2018). This is attributed to high photosynthetic efficiency and fast rate of diversion of sugars from source (leaf) to sink (fruit) which is different among the lines.…”
Section: Discussionmentioning
confidence: 86%